Composição, distribuição espacial, dinâmica de populações de peixes e estatística pesqueira na lagoa hipersalina de Araruama, RJ - Saad, Adriana Miguel (Universidade Federal de São Carlos, 2003)
The Araruama lagoon, located on the North East of Rio de Janeiro State, is the largest hyper saline lagoon in Brazil, covering an area of 200 km² and presenting a salinity degree between 35 and 65 . In 1994, structural analyses of the fish community in relation to composition, relative abundance, constancy, dominance, spatial distribution and diversity of species were made. The Araruama lagoon was divided in three areas according to fish spatial distribution, which in turn is related to the distribution of salinity in the lagoon. The first area was the channel that provides communication between the lagoon and the ocean. It was characterized as a eutrophic environment, presenting 37 degree of averaged salinity. The second area was considered a species adaptation zone, presenting 45 degree of average salinity. The third area was characterized as an oligotrophic hyper-saline system, presenting 57 degree of average salinity, comprising dominant and constant species. Results demonstrated that the fish community included 39 species classified as stenohaline, whose distribution was limited to near the ocean. These species were not tolerant of a large variation in salinity and They used to habit only in area 1. Euryhaline species, whose distribution occurred throughout the lagoon, were characterized by an osmo-regulation system that permited a large toleration to salinity variation. The euryhalines types was further subdivided into: (i) oligohaline species that tolerated moderate variation of salinity and were found in areas 1 e 2; (ii) holeurihaline species that moved freely among areas 1, 2 and 3, and also established populations in the lagoon and in the ocean, and (iii) polihalophylic species that tolerated a large variation in salinity, and moved freely among areas 1, 2 and 3, but were not establishing new populations, as demonstrated by their limited occurrence.
Keywords: Ictiologia; Ictiofauna; Araruama, Lagoa de (RJ); Estatística pesqueira; Pesca artesanal; CIENCIAS BIOLOGICAS::ECOLOGIA